Green synthesis, characterization of Radix Hedysari-mediated silver nanoparticles and their use for sensitive colorimetric detection of Pb2+ in the Yellow River medium. Issue 6 (26th January 2022) - Ji, Jiahui; Wu, Huifang; Wang, Donghan; Liu, Dan; Chen, Xinyue; Feng, Shilan
Abstract : Schematic diagram of the synthesis and application of RH–AgNPs. Abstract : In this study, a safe, rapid, and environment-friendly green synthesis of silver nanoparticles using the alcohol extract of Radix Hedysari (RH–AgNPs) was developed, the alcohol extract of Radix Hedysari (RH) acted as the reducing agent, stabilizer, and modifier. The main components of RH were determined using high-performance liquid chromatography (HPLC). The particle size and morphology of RH–AgNPs were optimized and characterized by a series of techniques. The size distribution, zeta potential, element distribution, and crystalline nature of RH–AgNPs were all determined. It was indicated that RH–AgNPs showed great sensitivity for lead ion (Pb 2+ ) detection with a limit of detection (LOD) of 1.5 μM with a wide range of 10–500 μM. The selectivity was also explored for common metal ions. RH–AgNPs were then applied to the detection of Pb 2+ in spiked Yellow River samples, and the possible mechanism is based on the crosslinking reaction between the hydroxide radical, carboxylate radical and Pb 2+ .